PENYALAHGUNAAN KEWENANGAN TINDAK PIDANA KORUPSI BERDASARKAN UNDANG-UNDANG ADMINISTRASI PEMERINTAHAN (Studi Kasus Putusan Pengadilan Tata Usaha Negara Jambi Nomor 2/P/PW/2017/PTUN.JBI) - Putri Sukmiani (2022)
Based on the Law Number 30 of 2014 concerning Government Administration, and the Supreme Court regulation have extended the absolute competence of the Administrative Court to examine elements of abuse of authority committed by state officials in carrying out their positions. However, this authority is not the only option given by law in Indonesia, which in addition there is also the authority of the general court to resolve the topic of abuse of authority that causes harm to the country. therefore, there is still ambiguity and overlap in laws related to abuse of authority which causes losses to state finances which ultimately has an impact on legal certainty and justice for related parties. This type of thesis research used normative juridical research that is descriptive. The Data used to answer the problems in this study were secondary data and primary data derived from library research. The results of the study found that the District Administrative Court was authorized to decide related elements of abuse of authority committed by the agency and/or government officials. The analysis of the state administration Case Number: 2/P/PW/2017/PTUN.JBI. not compatible with Perma No. 4 of 2015 because it did not meet the requirements, the new court is authorized to accept, examine, and decide the assessment of the application, after the results of the supervision of the government Internal Audit apparatus (APIP) and the court is authorized to accept, examine, and decide the assessment of the application for assessment of whether or not there was abuse of authority in the decisions and/or actions of government officials before the criminal process. The conclusion obtained was the analysis of the consideration of judges and the decision of the PTUN Jambi was wrong and not in accordance with what was mandated in Regulation No. 4 of 2015 (Perma No. 4 of 2015) on guidelines in the assessment of judicial elements of abuse of authority. It is recommended to the government to harmonize laws and regulations related to abuse of authority both in terms of criminal and administrative aspects of the government in order to achieve regulatory harmony.